A solid electrolyte with a doped modified layer, a preparation method thereof, and solid-state battery application

By introducing a doped modified layer into the sulfide solid electrolyte and regulating the electrochemical in situ ion embedding process, the redox reaction problem when the sulfide electrolyte comes into contact with the lithium metal negative electrode is solved, and the interface stability and electrochemical cycling performance are significantly improved.

CN118645681BActive Publication Date: 2025-03-18BEIJING UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410912547.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-09
Publication Date
2025-03-18
Estimated Expiration
2044-07-09

AI Technical Summary

Technical Problem

When the sulfide electrolyte comes into contact with the lithium metal negative electrode, a redox reaction will occur, forming an electron-ion mixing interface, hindering ion transport, and causing lithium dendrites to nucleate inside the electrolyte, causing battery short circuit. It is difficult for the prior art to effectively inhibit the growth of lithium dendrites.

Method used

By introducing a doped modified layer into the sulfide solid electrolyte, including Al, Mg, Fe, Zn, Sn, Ag, Cu, Se, Bi, Si, Mo and other elements, the electrochemical in-situ ion embedding process is regulated, so that the crystal plane spacing of the (111) crystal plane is within the range of 0.54nm~0.58nm, and chemical reactions and lithium dendrites are inhibited.

Benefits of technology

It effectively improves the interface stability of the sulfide solid electrolyte and the lithium metal negative electrode, reduces the generation of electronic products, enhances the electrochemical cycling performance, and reduces the interface impedance of the reaction between the electrolyte and lithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004934081750000111
    Figure BDA0004934081750000111
  • Figure BDA0004934081750000121
    Figure BDA0004934081750000121
Patent Text Reader

Abstract

A solid electrolyte with a doped modified layer and its preparation method and solid-state battery application, which relates to the field of new energy materials. It includes: a base material and a doped modified layer; the general formula of the base material is Li 7‑M PS 6‑M X M , X=Cl, Br, I, 1≤M≤1.6; the doping modification layer contains at least one element of Al, Mg, Fe, Zn, Sn, Ag, Cu, Se, Bi, Si, Mo; the interplanar spacing of the solid electrolyte (111) crystal plane is d(111), 0.54nm
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy materials, and in particular to a modification method of a sulfide electrolyte and application thereof. Background Art

[0002] With the rapid development of new energy vehicles and other industries, solid-state batteries are very promising due to their higher energy density and better safety. Sulfide solid electrolytes are ideal inorganic solid electrolyte materials due to their high ionic conductivity, good mechanical ductility and other characteristics.

[0003] However, when the sulfide electrolyte contacts the negative electrode lithium, a redox reaction will occur, generating an electron-ion mixed interface, which hinders ion transport. At the same time, the current distribution is uneven, causing lithium dendrites to nucleate inside the electrolyte, ultimately causing a battery short circuit. Existing intrinsic doping methods are difficult to effectively suppress the growth of lithium dendrites, and surface coating methods are limited by high costs and complex production procedures, and increasing the thickness of the electrolyte sheet is not conducive to achieving high energy density. (Existing intrinsic doping and surface coating methods have significant deficiencies in suppressing lithium dendrite growth and cost control). For example, CN202310074526.3 provides a method for synergistic modification of doping and coating, doping chloride (such as NbCl5), improving ionic conductivity, and stabilizing the interface to a certain extent. CN202110212520.9 provides a coating method, combining the electrolyte with aluminum salts, ammonium fluoride, etc., to improve conductivity. However, this type of method has a complex preparation process, cumbersome procedures, and limited performance improvement at high current density. Therefore, an efficient modification method for sulfide-based solid-state battery electrolytes is urgently needed to ensure the stability of their interface with lithium metal anodes. Summary of the invention

[0004] The present invention aims to provide a sulfide-based solid electrolyte material and a modification method and application thereof, so as to improve the stability of the interface between the sulfide-based solid electrolyte material and the lithium metal negative electrode during circulation.

[0005] In view of this, the present invention first provides a sulfide material, comprising: a base material and a doping modification layer;

[0006] The general formula of the matrix material is Li 7-M PS 6-M X M , X=Cl, Br, I, etc., where 1≤M≤1.6;

[0007] The doped and modified layer contains at least one element among Al, Mg, Fe, Zn, Sn, Ag, Cu, Se, Bi, Si, Mo, etc. For the sulfide solid electrolyte with the doped and modified layer, the interplanar spacing of the (111) crystal plane is d(111), satisfying 0.54 nm < d(111) < 0.58 nm.

[0008] Furthermore, the above-mentioned doped and modified layer is at least one of the above elements, preferably Mg, and the interplanar spacing obtained from its X-ray diffraction pattern is d = 0.547 nm.

[0009] For the sulfide solid electrolyte with the doped and modified layer, with the occurrence of the in-situ electrochemical ion insertion process, internal stress will be generated within the lattice, changing the d-spacing (interplanar spacing);

[0010] 2dsinθ = nλ (1)

[0011] Wherein, d is the interplanar spacing, λ is the wavelength of the incident light (λ = 0.15405 nm), and θ is the diffraction angle, which is obtained by testing the X-ray diffraction pattern.

[0012] Through a large number of experimental explorations, the present invention finds that by regulating the doping process and doping elements of the above-mentioned in-situ electrochemical doping, making the interplanar spacing of the crystal plane (111) of the above-mentioned sulfide solid electrolyte with the doped and modified layer satisfy the above relationship 0.54 nm < d(111) < 0.58 nm, the chemical reaction on the surface of the sulfide solid electrolyte material can be inhibited, and the electronic products of its reaction with the lithium metal negative electrode can be reduced, thereby improving the stability of the interface with the lithium metal negative electrode during the electrochemical cycling process.

[0013] The in-situ electrochemical ion insertion into the sulfide solid electrolyte includes the following elements: Through the ion radius table, taking the Li ion radius as a reference, doping elements can be selected from elements such as Al, Mg, Fe, Zn, Sn, Ag, Cu, Se, Bi, Si, Mo, etc. with ion radii larger than that of Li; Experiments have found that when doping contains at least one element among Al, Mg, Fe, Zn, Sn, Ag, Cu, Se, Bi, Si, Mo, etc., and when the interplanar spacing of the crystal plane (111) of the X-ray diffraction pattern satisfies 0.54 nm < d(111) < 0.58 nm, the stability of its interface with the lithium metal negative electrode can be better ensured; It not only ensures a stable crystal structure but also enables it to have excellent long-cycle performance during the electrochemical process.

[0014] The preparation method of a solid electrolyte with a doped and modified layer, characterized in that it adopts the in-situ electrochemical ion insertion method, including the following steps:

[0015] Step 1: Weigh the chloride-containing salt containing the doping element and the base material and mix them thoroughly by ball milling to obtain a modified electrolyte precursor; the ball milling speed is 250-400 rpm, preferably 300 rpm, and the ball milling time is 2-4 h, preferably 3 h;

[0016] Step 2: cold press the modified electrolyte precursor obtained in step 1 into a thin sheet, and then perform constant current charge and discharge. After one charge and discharge, a sulfide solid electrolyte with an in-situ electrochemical ion embedding and a doped modified layer is obtained; the charge and discharge current density is 0.05-2 mA cm -2 The charging and discharging time are both 30 min-90 min, for example, 60 min.

[0017] In the further step 1, the chloride-containing salt is selected from chlorides, chlorates, hypochlorites, perchlorates, chlorine oxides, etc.

[0018] The amount of the chloride-containing salt containing the doping element and the matrix material is adjusted according to the interplanar spacing d(111) of the crystal plane (111) in the final product to meet 0.54nm. <d(111)<0.58nm。

[0019] The modified electrolyte precursor was placed in a vacuum drying oven at 60° C. for 12 hours.

[0020] Further preferred is step 2, cold pressing the modified electrolyte precursor into a sheet with a thickness of 200-400 microns at a pressure of 6 MPa, placing lithium metal sheets on both sides of the sheet and assembling them into a mold battery; connecting the mold battery to a blue electric charge and discharge test system for constant current charge and discharge, and obtaining a sulfide solid electrolyte with an in-situ electrochemical ion embedding doped modified layer after one charge and discharge.

[0021] Continue to perform constant current charge and discharge condition cycle performance test with the above device (the same constant current charge and discharge conditions as above can be used) to obtain a stable cycle number.

[0022] The preparation method of the matrix material is as follows: Li2S, high temperature gas phase raw materials and LiX are pre-mixed, ball-milled and sintered in sequence under a protective atmosphere to obtain the matrix material. The protective atmosphere can be a nitrogen atmosphere or an argon atmosphere. Preferably, the inert atmosphere is an argon atmosphere.

[0023] Preferably, the high-temperature gas-phase raw material is a compound containing P and S that can be fully gasified at above 300°. Specifically, the high-temperature gas-phase raw material is phosphorus pentasulfide.

[0024] The ball milling treatment is performed by using a planetary ball mill for ball milling mixing. Preferably, the rotation speed of the planetary ball mill is 200 to 500 rpm, and the ball milling time is preferably 40 hours.

[0025] Preferably, after ball milling, the raw material is subjected to high temperature treatment at a heating rate of 3°C / min, the temperature is raised to 550°C, and the temperature is kept for 5h.

[0026] The present invention finds that doping elements with ionic radius larger than that of Li, such as Al, Mg, Fe, Zn, Sn, Ag, Cu, Se, Bi, Si, Mo, etc., can appropriately increase the interplanar spacing of the (111) crystal plane of the sulfide solid electrolyte. However, when the interplanar spacing is greater than 0.58nm, the original PS4 3- The structure affects the continuity of the ion migration channel and introduces stress concentration points, which will cause the material to pulverize during the charge and discharge process. Defects begin to appear at the electrolyte interface, increasing the impedance of the interface between the electrolyte and the lithium metal negative electrode, leading to a decrease in performance.

[0027] In the above preferred embodiment, when the sulfide solid electrolyte is electrochemically in situ, especially after Mg ion insertion, the introduction of Mg will reduce the unbonded S in the electrolyte during the electrochemical cycle. - With Li + The reaction inhibits the generation of Li2S, an electronic product of oxidative decomposition, which plays a positive role in reducing interfacial impedance and improving the stable deposition of lithium metal anode.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention performs ion electrochemical doping surface treatment on a sulfide solid electrolyte at room temperature. The ion electrochemical doping surface treatment mainly uses elements larger than the radius of lithium ions for doping, which inhibits the oxidation (charging process) from generating decomposed electronic products (Li2S). The X-ray diffraction pattern lattice spacing of the sulfide solid electrolyte with an interface doping modification layer is larger than the crystal plane spacing of the original undoped sulfide electrolyte, providing more channels for the migration of lithium ions and accelerating the migration rate of lithium ions. Through the electrochemical doping treatment, while maintaining the phase stability of the electrochemical cycle process, the electronic products generated by the reaction of the sulfide solid electrolyte with an interface doping modification layer and lithium are reduced, and the stability of the interface with the negative electrode is improved. The method has lower cost and simple process, can be directly integrated into the assembly process of the battery, and the sulfide electrolyte is electrochemically modified in situ, which plays a great value and potential in the large-scale production and application of solid-state batteries represented by sulfide-based batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the interface impedance diagram of Example 2.

[0031] Figure 2 It is the performance diagram of comparative example 1 and embodiment 2. DETAILED DESCRIPTION

[0032] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. If no specific techniques or conditions are specified in the examples, they are all conventional methods or carried out according to the techniques or conditions described in the literature of the field, or according to the product instructions. If the manufacturers of the reagents and instruments used are not specified, they are all conventional products that can be purchased through regular channels.

[0033] The sulfide solid electrolyte with an interface doping modification layer prepared in this embodiment can be used as a solid electrolyte in solid-state batteries.

[0034] Comparative Example 1

[0035] This comparative example provides a Li6PS5Cl prepared by a traditional solid phase sintering method, which is specifically prepared as follows:

[0036] Li6PS5Cl (LPSCl) solid electrolyte powder was synthesized by solid-state reaction method. The raw materials were Li2S (99.9%, Aladdin), P2S5 (99.9%, Aladdin) and LiCl (99.9%, Aladdin). First, the raw materials were weighed according to the stoichiometric ratio of LPSCl and then ball-milled in a zirconia-lined vacuum tank to obtain the LPSCl electrolyte precursor. Ball milling conditions: ball-to-material ratio of 40:1, rotation speed of 200rpm; ball milling time of 6h. Then the LPSCl electrolyte precursor was placed in a closed quartz crucible and heat-treated under argon protection atmosphere, with a heating rate of 5℃ / min, heated to 500℃, and sintering time of 8h. The obtained LPSCl electrolyte matrix material was ground and sieved using a 200-mesh stainless steel screen. All environments were carried out in an inert protection or glove box with H2O and O2 content less than 1ppm.

[0037] Comparative Example 2

[0038] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with magnesium chloride MgCl2 by ball milling (wherein the mass of Mg element accounts for 8% of the mass of Li6PS5Cl) until it is uniform. Then assemble the lithium symmetric battery at 0.056 mA cm -2 A constant current charge and discharge was performed at a current density of 0.056 mAh cm -2 .

[0039] Comparative Example 3

[0040] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix bismuth oxychloride BiOCl with it by ball milling (wherein the mass of Bi element accounts for 8% of the mass of Li6PS5Cl) until it is uniform. Then assemble the lithium symmetric battery at 0.084 mA cm -2 A constant current charge and discharge was performed at a current density of 0.084 mAh cm -2 .

[0041] Comparative Example 4

[0042] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix zinc chlorate Zn(ClO3)2 with it by ball milling (wherein the mass of Zn element accounts for 6% of the mass of Li6PS5Cl) until it is uniform. Then assemble the lithium symmetric battery at 0.096 mA cm -2 A constant current charge and discharge was performed at a current density of 0.096 mAh cm -2 . .

[0043] Comparative Example 5

[0044] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with silver chlorate AgClO3 by ball milling (wherein the mass of Ag element accounts for 7% of the mass of Li6PS5Cl) until it is uniform. Then assemble the lithium symmetric battery at 0.1 mA cm -2 A constant current charge and discharge was performed at a current density of 0.1 mAh cm -2 .

[0045] Comparative Example 6

[0046] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with molybdenum chloride MoCl3 by ball milling (wherein the mass of Mo element accounts for 5.5% of the mass of Li6PS5Cl) until it is uniform. Then assemble the lithium symmetric battery at 0.084mAcm -2 A constant current charge and discharge was performed at a current density of 0.084 mAh cm -2 .

[0047] Comparative Example 7

[0048] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix copper perchlorate Cu(ClO4)2 with it by ball milling (the mass of Cu element accounts for 6.5% of the mass of Li6PS5Cl) until it is uniform. Then assemble the lithium symmetric battery at 0.144mAcm -2 A constant current charge and discharge was performed at a current density of 0.144 mAh cm-2 .

[0049] Example 1

[0050] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with magnesium chloride MgCl2 by ball milling (wherein the mass of Mg element accounts for 2% of the mass of Li6PS5Cl) until it is uniform. Then assemble the lithium symmetric battery at 0.056 mA cm -2 A constant current charge and discharge was performed at a current density of 0.056 mAh cm -2 .

[0051] Example 2

[0052] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix magnesium perchlorate Mg(ClO4)2 with it by ball milling (wherein the mass of Mg element accounts for 2% of the mass of Li6PS5Cl) until it is uniform. Then assemble the lithium symmetric battery at 0.084 mA cm -2 A constant current charge and discharge was performed at a current density of 0.084 mAh cm -2 .

[0053] Example 3

[0054] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix zinc chlorate Zn(ClO3)2 with it by ball milling (where the mass of Zn element accounts for 2% of the mass of Li6PS5Cl) until it is uniform. Then assemble the battery and conduct it at 0.28 mA cm -2 A constant current charge and discharge was performed at a current density of 0.28 mAh cm -2 .

[0055] Example 4

[0056] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix bismuth oxychloride BiOCl with it by ball milling (wherein the mass of Bi element accounts for 2.5% of the mass of Li6PS5Cl) until it is uniform. Then assemble the lithium symmetric battery at 0.056 mA cm -2 A constant current charge and discharge was performed at a current density of 0.056 mAh cm -2 .

[0057] Example 5

[0058] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with tin tetrachloride SnCl4 by ball milling (where the mass of Sn element accounts for 3% of the mass of Li6PS5Cl) until it is uniform. Then assemble the battery at 0.144 mA cm -2 A constant current charge and discharge was performed at a current density of 0.144 mAh cm -2 .

[0059] Example 6

[0060] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with germanium tetrachloride GeCl4 (where the mass of Ge element accounts for 2% of the mass of Li6PS5Cl) by ball milling until it is uniform. Then assemble the battery at 0.096mAcm -2 A constant current charge and discharge was performed at a current density of 0.096 mAh cm -2 .

[0061] Example 7

[0062] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with silicon tetrachloride SiCl4 (wherein the mass of Si element accounts for 2% of the mass of Li6PS5Cl) by ball milling until it is uniform. Then assemble the battery at 0.056mAcm -2 A constant current charge and discharge was performed at a current density of 0.056 mAh cm -2 .

[0063] Example 8

[0064] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with selenium tetrachloride SeCl4 (where the mass of Se element accounts for 2% of the mass of Li6PS5Cl) by ball milling until it is uniform. Then assemble the battery at 0.096 mA cm -2 A constant current charge and discharge was performed at a current density of 0.096 mAh cm -2 .

[0065] Example 9

[0066] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix copper perchlorate Cu(ClO4)2 with it by ball milling (the mass of Cu element accounts for 2% of the mass of Li6PS5Cl) until it is uniform. Then assemble the battery at 0.056mAcm -2 A constant current charge and discharge was performed at a current density of 0.056 mAh cm -2 .

[0067] Example 10

[0068] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with molybdenum chloride MoCl3 (where the mass of Mo element accounts for 3% of the mass of Li6PS5Cl) by ball milling until it is uniform. Then assemble the battery at 0.084mAcm -2 A constant current charge and discharge was performed at a current density of 0.084 mAh cm -2 .

[0069] Embodiment 11

[0070] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with iron chlorate Fe(ClO3)2 by ball milling (where the mass of Fe element accounts for 2% of the mass of Li6PS5Cl) until it is uniform. Then assemble the battery at 0.056mAcm -2 A constant current charge and discharge was performed at a current density of 0.056 mAh cm -2 .

[0071] Example 12

[0072] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix it with silver chlorate AgClO3 (where the mass of Ag element accounts for 4% of the mass of Li6PS5Cl) by ball milling until it is uniform. Then assemble the battery at 0.096 mA cm -2 A constant current charge and discharge was performed at a current density of 0.096 mAh cm -2 .

[0073] Embodiment 13

[0074] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix magnesium perchlorate Mg(ClO4)2 with it by ball milling (wherein the mass of Mg element accounts for 5% of the mass of Li6PS5Cl) until it is uniform. Then assemble the battery at 0.144 mA cm -2 A constant current charge and discharge was performed at a current density of 0.144 mAh cm -2 .

[0075] Embodiment 14

[0076] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix bismuth oxychloride BiOCl with it by ball milling (wherein the mass of Bi element accounts for 4% of the mass of Li6PS5Cl) until it is uniform. Then assemble the battery at 0.056 mA cm -2A constant current charge and discharge was performed at a current density of 0.056 mAh cm -2 .

[0077] Embodiment 15

[0078] Take the Li6PS5Cl electrolyte matrix material prepared in Comparative Example 1, and mix zinc chlorate Zn(ClO3)2 with it by ball milling (where the mass of Zn element accounts for 3.5% of the mass of Li6PS5Cl) until it is uniform. Then assemble the battery at 0.084mAcm -2 A constant current charge and discharge was performed at a current density of 0.084 mAh cm -2 .

[0079] The solid electrolyte test performance of each embodiment and comparative example is as follows, and the results are shown in Table 1 below:

[0080] Table 1

[0081]

[0082]

Claims

1. A sulfide solid electrolyte having a doped modified layer, characterized in that: include: Base material and doping modification layer; The general formula of the matrix material is Li 7-M PS 6-M X M , X = Cl, Br, I, where 1 ≤ M ≤ 1.6; The doped modified layer contains at least one element of Mg, Fe, Zn, Sn, Ag, Cu, Se, Bi, Si, and Mo; The sulfide solid electrolyte with a doped modified layer has a (111) crystal plane spacing d(111) of 0.54 nm. <d(111)<0.58nm; The method for preparing a sulfide solid electrolyte adopts an electrochemical in-situ ion embedding method, comprising the following steps: Step 1: Weigh the chlorine-containing substance containing the doping element and the base material and mix them thoroughly by ball milling to obtain a modified electrolyte precursor; Step 2: The modified electrolyte precursor obtained in step 1 is cold pressed into a thin sheet, and then constant current charge and discharge are performed. After one charge and discharge, a sulfide solid electrolyte with an in-situ electrochemical ion embedding and a doped modified layer is obtained; the charge and discharge current density is 0.05~2mAcm -2 The charging and discharging time are both 30min-90min.

2. A sulfide solid electrolyte with a doped modified layer according to claim 1, characterized in that: The doped modified layer is Mg, and the interplanar spacing obtained from the X-ray diffraction diagram is d=0.547nm.

3. The method for preparing a sulfide solid electrolyte having a doped modified layer according to any one of claims 1 to 2, characterized in that: The electrochemical in-situ ion embedding method includes the following steps: Step 1: Weigh the chlorine-containing substance containing the doping element and the base material and mix them thoroughly by ball milling to obtain a modified electrolyte precursor; Step 2: The modified electrolyte precursor obtained in step 1 is cold pressed into a thin sheet, and then constant current charge and discharge are performed. After one charge and discharge, a sulfide solid electrolyte with an in-situ electrochemical ion embedding and a doped modified layer is obtained; the charge and discharge current density is 0.05~2mAcm -2 The charging and discharging time are both 30min-90min.

4. The method according to claim 3, characterized in that In step 1, the chlorine-containing substance is selected from chloride, chlorate, hypochlorite, perchlorate, and chlorine oxide; the ball milling speed is 250-400 rpm, and the ball milling time is 2-4 h.

5. The method according to claim 4, characterized in that The ball milling speed was 300 rpm and the ball milling time was 3 h.

6. The method according to claim 3, characterized in that In step 1, the amount of the chloride-containing salt containing the doping element and the matrix material is adjusted according to the interplanar spacing d(111) of the crystal plane (111) in the final product to meet 0.54nm. <d(111)<0.58nm; The sulfide solid electrolyte with a doped modified layer generates internal stress in the lattice as the electrochemical in-situ ion embedding process occurs, changing the d-spacing, i.e. the interplanar spacing; (1) Where d is the interplanar spacing, is the wavelength of incident light, λ = 0.15405nm, is the diffraction angle, obtained from the X-ray diffraction pattern test.

7. The method according to claim 3, characterized in that Step 2: Cold-press the modified electrolyte precursor into a sheet with a thickness of 200-400 microns at a pressure of 6 MPa, place lithium metal sheets on both sides of the sheet and assemble them into a mold battery; connect the mold battery to the Blue Electric charge and discharge test system for constant current charge and discharge, and after one charge and discharge, a sulfide solid electrolyte with an in-situ electrochemical ion embedding and a doped modified layer is obtained.

8. The method according to claim 3, characterized in that In step 1, the preparation method of the matrix material is as follows: Li2S, a high temperature gas phase raw material and LiX are pre-mixed, ball-milled and sintered in sequence under a protective atmosphere to obtain a matrix material, wherein the protective atmosphere is a nitrogen atmosphere or an argon atmosphere; The high-temperature gas-phase raw material is a compound containing P and S that can be fully gasified at above 300°. Specifically, the high-temperature gas-phase raw material is phosphorus pentasulfide; The ball milling treatment is to use a planetary ball mill for ball milling mixing, the rotation speed of the planetary ball mill is 200~500rpm, and the ball milling time is 40 hours; After ball milling, the raw materials were subjected to high temperature treatment at a heating rate of 3°C / min, the temperature was raised to 550°C, and the temperature was kept for 5h.

9. Use of the sulfide solid electrolyte with a doped modified layer as claimed in any one of claims 1 to 2 as a solid electrolyte for a lithium battery.

10. A solid-state battery, characterized in that: The invention comprises a lithium metal electrode and a sulfide solid electrolyte with a doped modified layer as claimed in any one of claims 1 to 2.

Citation Information

Patent Citations

  • A sulfide solid electrolyte, its preparation method and application

    CN112768761B

  • Method for modifying sulfide electrolyte by doping and coating synergistically and application of sulfide electrolyte

    CN115954536A

  • Solid-state lithium battery in-situ electrochemical passivation and repair method

    CN117613366A

  • Solid electrolyte, and lithium ion power storage element

    JP2020119782A